Didactic in emergency remote teaching in the view of undergraduate students in brazilian Center-West - Libâneo, José Carlos (2022)
The text is the result of empirical research named Remote teaching of Didactics in undergraduate courses at public universities: the students' view, promoted by the National Association of Didactics and Teaching Practices - Andipe, based on the analysis of responses to an online questionnaire, in the context of national. In this article, we analyze the vision of 78 undergraduate students from 10 public universities in the Brazilian Midwest regarding didactic discipline in emergency remote teaching (ERE) during the period of the SARS-CoV-2 Coronavirus pandemic (2020-2021). The text proposes the discussion of issues raised by students and analyzes challenges and possibilities for rethinking the teaching of post-pandemic didactics. The research identified that students recognize the quality of teaching work and pedagogical-didactic studies during the ERE and its critical and contextualized approach. However, it allows us to apprehend, in the students' view, the persistence in teaching didactics from the instrumental view. At the end, the article brings considerations about the objectives and contents of Didactics teaching, the relationship between technology and post-pandemic teaching and the perspectives for rethinking the discipline in teacher training courses.